Preliminary review of the genus Stenotarsus Perty (Coleoptera: Endomychidae) from México, Guatemala and Belize, with descriptions of twelve new species - Arriaga-Varela, Emmanuel; Zaragoza-Caballero, Santiago; Tomaszewska, Wioletta; Navarrete-Heredia, Jose Luis (Zootaxa, 2013)
A preliminary review of the species of Stenotarsus Perty from México, Guatemala and Belize is presented. Twenty-seven species are recorded from the region including 12 new species described here: Stenotarsus cortesi sp. nov. (Jalisco), S. incisus sp. nov.Quetzaltenango, Chiapas, Oaxaca, Veracruz),kafkai sp. nov.Veracruz),mesoamericanus sp. nov.Chiapas, Puebla),mexicanus sp. nov.Veracruz),molgorae sp. nov.Jalisco),monterrosoi sp. nov.Izabal),parallelicornis sp. nov. (Veracruz), S. raramuri sp. nov.Durango, Jalisco),rulfoi sp. nov. (Jalisco),shockleyi sp. nov.Veracruz),spiropenis sp. nov. (Jalisco). Stenotarsus circumdatus Gerstaecker,discipennis Gorham and S. tarsalis Gorham are synonymized with S. globosus Guérin-Méneville.distinguendus Arrow is synonymized with S. sallaei Gorham. Stenotarsus pilatei Gorham is synonymized with S. militaris Gerstaecker. Lectotypes are designated for: Stenotarsus circumdatus Gerstaecker,distinguendus Arrow, Stenotarsus exiguus Gorham,globosus Guérin-Méneville,guatemalae Arrow,discipennis Gorham, Stenotarsus lemniscatus Gorham, Stenotarsus militaris Gerstaecker, Stenotarsus rubrocinctus Gerstaecker, Stenotarsus sallaei Gorham, Stenotarsus tarsalis Gorham, Stenotarsus thoracicus Gorham. A key to the species in this region is provided. Species are described in detail and illustrated, and habits and habitats are given when available.